The problem of reason and revelation in the thought of Ibn Taymiyyah - Yettou, Ali (The International tax journal, 2026)
Shaykh al-Islam ibn Taymiyyah (661/1263 - 728/1328), the famous Muslim scholar. A reformer, Ibn Taymiyyah sought the return of Muslims to Islam; by returning to original sources, the Qur'an, the Sunnah, and the way of the companions. Until the Muslim returns to the net religion, he finds a problem between reason and revelation (Text: Quran and Sunnah); thus, Ibn Taymiyyah came and dealt with this problem, which is what this article discussed.